The Role of Multiwall Carbon Nanotubes in Cu-BTC Metal-Organic Frameworks for CO2 Adsorption - Ullah, S. (Chinese Chemical Society Taiwan, 2016)
The discovery of natural gas fields with a high content of CO2 in world gas reservoirs poses new challenges for CO2 capture. This work investigates the use of the metal-organic framework (MOF) Cu-BTC and hybrid MWCNTs@Cu-BTC for CO2 adsorption. Cu-BTC and hybrid MWCNTs@Cu-BTC were synthesized by the solvothermal method. The results of imaging of intact MOF pores in Cu-BTC and hybrid MWCNTs@Cu-BTC nanocrystals by high-resolution transmission electron microscopy (HRTEM) under liquid nitrogen conditions are presented. Physical characterizations of the solid adsorbents were made by using a selection of different techniques, including field-emission scanning electron microscopy (FESEM), X-ray powder diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), BrunauerâEmmetâTeller (BET) surface area, and CO2 adsorption and physisorption measurements. HRTEM and FESEM confirmed that Cu-BTC has an octahedral shape and that the surface morphology of Cu-BTC changes by the intercalation of MWCTNs. The results show that the modified Cu-BTC improved the CO2 adsorption compared to pure Cu-BTC. The increase in the CO2 uptake capabilities of hybrid MWCNTs@Cu-BTC was ascribed to the intercalation of MWCNTs with Cu-BTC crystals. The CO2 sorption capacities of Cu-BTC and hybrid MWCNTs@Cu-BTC were found to increase from 1.91701 to 3.25642 mmol/g at ambient conditions. Â© 2016 The Chemical Society Located in Taipei & Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim